Gilbert Achcar on the Arab Upheaval—Facts and Fiction. Issue 1 (2nd January 2016) - Achcar, Gilbert; Matta, Nada
Abstract: Gilbert Achcar discusses with Nada Matta the crisis in the Middle East and North Africa and points out the responsibilities of all elite actors involved, both external and internal to the region. This interview was first published online by Jacobin on 17 December 2015. The Journal of Balkan and Near Eastern Studies thanks Jacobin for allowing reproduction of the interview here.